Women's perception about the climate period and menopause (Research, Society and Development, 2022)
Objective: To understand the perception of women in the climacteric and menopause period. Methodology: Qualitative exploratory-descriptive study. The interviewees were selected based on their relationship with a religious institution located in the district of Ivailândia-PR, the inclusion criterion for eligibility was: women in the climacteric or menopause period. The interviews were guided by the guiding question: Tell me about your experience in the climacteric period and menopause. Data collection was carried out between April and May 2022, they were carried out at home, recorded and transcribed in full, the interpretation and analysis of the data were based on Bardin's content analysis, in the thematic modality. Results: Ten women aged between 46 and 59 years participated in the research. The testimonies originated four thematic categories. 1 - “Level of knowledge about the climacteric period and menopause”, identified that most climacteric women did not know the meaning of climacteric. 2 - “Perceived physiological changes”, the most cited changes were: hot flashes, insomnia, stress, anxiety. 3 - “Perception about the climacteric/menopause”, the main ones reported were: decreased metabolism and neuropsychological symptoms. 4 - “Alternative treatments used by women in the climacteric/menopause”, the most mentioned treatment was the natural ones, such as blackberry capsule and white blackberry extract. Conclusion: Women have a deficit of knowledge about the subject, each one goes through this period in a unique way. It is up to the nurse as an educating agent to help them get to know, demystify and reframe this new phase.